2021
DOI: 10.1186/s12864-021-07811-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long noncoding RNAs reveals the effects of dinotefuran on the brain in Apis mellifera (Hymenopptera: Apidae)

Abstract: Background Dinotefuran (CAS No. 165252–70-0), a neonicotinoid insecticide, has been used to protect various crops against invertebrate pests and has been associated with numerous negative sublethal effects on honey bees. Long noncoding RNAs (lncRNAs) play important roles in mediating various biological and pathological processes, involving transcriptional and gene regulation. The effects of dinotefuran on lncRNA expression and lncRNA function in the honey bee brain are still obscure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…All four neonicotinoid active ingredients had inhibitory effects on acetylcholinesterase activity [31]. The KEGG analysis results revealed that most of the DEGs were related to material metabolism and were mainly enriched in the fatty acid metabolism, amino acid metabolism, insect hormone synthesis, nucleic acid metabolism, and other metabolic pathways, similar to the results reported that differentially expressed lncRNAs in dinotefuran-treated groups enriched in carbohydrate and protein metabolism [18].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…All four neonicotinoid active ingredients had inhibitory effects on acetylcholinesterase activity [31]. The KEGG analysis results revealed that most of the DEGs were related to material metabolism and were mainly enriched in the fatty acid metabolism, amino acid metabolism, insect hormone synthesis, nucleic acid metabolism, and other metabolic pathways, similar to the results reported that differentially expressed lncRNAs in dinotefuran-treated groups enriched in carbohydrate and protein metabolism [18].…”
Section: Discussionsupporting
confidence: 75%
“…A previous study found that S-dinotefuran's acute oral toxicity to juvenile worker bees is higher than that of R-dinotefuran, while the inhibitory effect of R-dinotefuran on honeybees' learning and memory ability was greater than that of S-dinotefuran, which may be associated with high expression of SERCA, Kca, and Maxik genes [17]. A recent study indicated that when young adult bees were exposed to dinotefuran, differentially expressed lncRNAs were mainly involved in development and the immune response [18]. However, to the best of our knowledge, there is no information about whether the mRNA expression profile of bees changes after treatment with a sublethal dose of dinotefuran.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that some lncRNAs can modulate cell signal transduction and biological processes by influencing downstream components of the MAPK pathway [ 47 ]. LncRNAs were involved in the hippo and TGF- β signaling pathways [ 21 ]. In summary, these analysis indicate that lncRNAs may affect the relevant reactions of honeybees to heat stress by regulating components of signal transduction pathways and signaling molecules, such as kinases and transcription factors, or by mediating the regulation of signaling molecules, such as mRNA-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the GSEA function ( Subramanian et al., 2005 ) was applied for gene set enrichment analysis considering the DESeq2 log2FoldChange of all analysed genes and the function emapplot was used for result visualization ( Reimand et al., 2019 ). This method was used in other recently studies on bee transcriptomes ( Chen et al., 2021 ; Holman et al., 2019 ; Huang et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%